1997
DOI: 10.12968/jowc.1997.6.5.222
|View full text |Cite
|
Sign up to set email alerts
|

Pain in venous leg ulcers

Abstract: A prospective study was conducted to assess the prevalence, severity and diagnostic utility of pain in patients with venous leg ulcers. A semi-structured questionnaire was completed by 140 consecutive patients in two specialist centres caring for patients with leg ulcers. A high proportion (64%) of the 94 patients with ulcers of purely venous aetiology reported severe pain; 50% of these patients were taking either mild analgesia or none at all. In 10 of 72 cases, leg elevation made the pain worse. Venous ulce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(69 citation statements)
references
References 7 publications
2
64
0
3
Order By: Relevance
“…Our results are supported by those of Hofman et a1. [13] who found that 82% of 94 patients with venous ulcers reported distressing to excruciating pain, which in general was inadequately controlled. We believe that pain is common in all patients with venous ulcers.…”
Section: The Sf-mpqmentioning
confidence: 99%
“…Our results are supported by those of Hofman et a1. [13] who found that 82% of 94 patients with venous ulcers reported distressing to excruciating pain, which in general was inadequately controlled. We believe that pain is common in all patients with venous ulcers.…”
Section: The Sf-mpqmentioning
confidence: 99%
“…The exact prevalence of pain is unknown, but recent studies have reported that 17-65% of patients experience severe or continuous pain associated with a leg ulcer (2,3). There are different pathologies that might cause pain associated with leg ulcérations (e.g.…”
mentioning
confidence: 99%
“…They can be painful, malodorous and have been shown to severely impact on patients' mobility and quality of life. [8][9][10] In severe cases, ulceration can lead to limb amputation. 11 Leg ulcers are also costly.…”
Section: Leg Ulcersmentioning
confidence: 99%
“…Longer ulcer duration is associated with longer time to healing and is an important prognostic variable; 9,47 we therefore recorded duration of reference ulcer at baseline based on participant report.…”
Section: Duration Of Reference Ulcermentioning
confidence: 99%